Histoire et parcours de vie : la perception des changements sociohistoriques - Aude Martenot; Stefano Cavalli (Temporalités)
This paper focuses on the memories of the past as reported by adults aged between 20-24 and 80-84. Which socio-historical changes and events occurring during their own lifetime do they retain as particularly striking ? Results are based on two surveys conducted in Geneva in 2004 and 2009, and allow a double comparison : between age groups (or cohorts) on the one hand, between the answers five years apart on the other hand. Some events (World War II, the fall of the Berlin Wall, for example, or 9/11) are particularly recalled by groups whe were entering adulthood at the time they occurred. Thus, the perception of a historic event varies with the age of individuals ; furthermore, changes that take place between ages ten and thirty have a great impact on memory. However, this is not a universal mechanism but depends on several conditions, including the fact that history has ushered in one or more changes at the same time.